Ethnic aspects of rheumatic diseases - Zemfira Sadullayevna Alekberova; F I Izmailova; M T Kudayev; E L Nasonov (Современная ревматология)
In relation to the ethnicity of patients, the clinical, genetic, and therapeutic aspects of rheumatic diseases (RD), Behcet’s disease and systemic lupus erythematosus in particular, are extensively used in the literature. Ethnicity is a topical problem that must be considered when solving both the clinical and therapeutic problems in patients with RD.